DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON CANVA FOR EDUCATION TO IMPROVE DIGITAL LITERACY SKILLS IN SOLAR SYSTEM MATERIAL IPAS PROJECT - Wulandari, Herlina Tri; Sutama (Jurnal Pendidikan Ilmu Sosial, 2025)
The background of this study is based on the low level of digital literacy among students, which is influenced by the lack of innovative learning media and the limited ability of teachers to develop attractive digital media. Canva for Education was chosen as a solution because it provides easy-to-access interactive design features and supports collaborative and creative learning. This research aims to develop interactive learning media based on Canva for Education to improve students' digital literacy skills in IPAS projects at vocational high schools (SMK). The contribution of this research is the development of an innovative project-based learning method that is relevant to educational needs in the digital era, where this research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model to create interactive learning media. The research subjects were 33 students from class X AKL 3 at SMK Negeri 4 Klaten in the 2024/2025 academic year. The developed media was deemed highly suitable by subject matter experts (86%) and media experts (83%). Following implementation, the media received positive feedback from students and teachers, particularly regarding ease of use, increased motivation, and student engagement in learning. Effectiveness testing showed significant results, with an N-Gain score of 0.75 (high category) from pre-test and post-test scores. This indicates a substantial improvement in students' digital literacy skills after using the interactive Canva-based media. Overall, this study concludes that the interactive Canva for Education learning media is effective, practical, and suitable for supporting digital literacy in the IPAS project.